Identification, expression, and functional analysis of Hsf and Hsp20 gene families in Brachypodium distachyon under heat stress - Li,Na; Jiang,Min; Li,Peng; Li,Xiwen (PeerJ, 2021)
Background The heat shock factor (Hsf) and small heat shock protein (sHsp, also called Hsp20) complex has been identified as a primary component in the protection of plant cells from ubiquitous stresses, particularly heat stress. Our study aimed to characterize and analyze the Hsf and Hsp genes in Brachypodium distachyon, an annual temperate grass and model plant in cereal and grass studies. Results We identified 24 Hsf and 18 Hsp20 genes in B. distachyon and explored their evolution in gene organization, sequence features, chromosomal localization, and gene duplication. Our phylogenetic analysis showed that BdHsfs could be divided into three categories and BdHsp20s into ten subfamilies. Further analysis showed that the 3’UTR length of BdHsp20 genes had a negative relationship with their expression under heat stress. Expression analyses indicated that BdHsp20s and BdHsfs were strongly and rapidly induced by high-temperature treatment. Additionally, we constructed a complex regulatory network based on their expression patterns under heat stress. Morphological analysis suggested that the overexpression of five BdHsp20 genes enhanced the seed germination rate and decreased cell death under high temperatures. Conclusion Ultimately, our study provided important evolutionary and functional characterizations for future research on the regulatory mechanisms of BdHsp20s and BdHsfs in herbaceous plants under environmental stress.
Keywords: Heat shock protein; Heat shock factor; Evolution; Seed germination; Brachypodium distachyon; Correlation analysis